(untitled) - Food and Agriculture Organization of the United Nations (Rome, Italy, 2005)
Adopted by the 123rd session of the FAO Council in November 2002, this work talks about the international code of conduct
Keywords: Pesticides,Pesticides,Thuốc trừ sâu,Thuốc trừ sâu; Application,Law and legislation,Luật và pháp chế